Integrating out natural disaster shocks - Franziska Bremus; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
We study the role of international financial integration in buffering natural disaster shocks, using a large sample of advanced and emerging economies. Conditioning on such exogenous events addresses the endogeneity between financial structures and economic conditions. We document that integration improves shock absorption: output, consumption, and investment are significantly higher after a shock in states of high integration than in states of low integration. However, the benefits of international risk sharing mostly come to advanced economies. Emerging markets only profit from more integration if they have good institutions or high debt assets, whereas higher debt liabilities weaken the recovery.
Keywords: Q54; E44; F36; F62; G11; G15; 330; Financial integration; natural disasters; international risk sharing; dynamic panel model; emerging markets